(untitled) (Genius Repository, 2023)
The article analyzes the development of traditional Japanese garden art during the Muromachi period using the example of one of the best Japanese traditional gardens - Saihoji Temple. The influence of Zen Buddhism on the nature, character and composition of the Saihoji Temple Garden is analyzed